Asymptotic equivalence of solutions of linear Itô stochastic systems - Krenevych, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate the problem of the asymptotic equivalence of stochastic systems of linear ordinary equations and stochastic equations in the sense of mean square and with probability one.